2004
DOI: 10.9746/sicetr1965.40.415
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-time Model Identification by Using Adaptive Observer

Abstract: This paper proposes a new method of continuous-time model identification from sampled I/O data by using an adaptive observer. The boundedness of the parameter estimate and the exponential convergence of the parameter estimate error to 0 under the PE assumption are guaranteed. In order to identify the plant from a finite number of I/O data, an adaptive observer of a backward system is also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The proposing adaptive observer is based on the structure depicted in Fig. 1, in which there is an estimation mechanism of the intersample output (Ikeda et al, 2006a). When the parameter estimateθ i is a constant vector, the continuoustime signals z i (t) can be easily discretized without any approximations because of the zeroth order hold input assumption.…”
Section: Adaptive Observer For the Estimation Of A Continuous-time Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The proposing adaptive observer is based on the structure depicted in Fig. 1, in which there is an estimation mechanism of the intersample output (Ikeda et al, 2006a). When the parameter estimateθ i is a constant vector, the continuoustime signals z i (t) can be easily discretized without any approximations because of the zeroth order hold input assumption.…”
Section: Adaptive Observer For the Estimation Of A Continuous-time Modelmentioning
confidence: 99%
“…by usingz iΔ [k] andz iν [k] in (20). It can be shown that ε iΔ → 0 whenθ i → θ * (Ikeda et al, 2006a). The asymptotic bias is caused by ε iν [k] and is analyzed in the next section.…”
Section: Adaptive Observer For the Estimation Of A Continuous-time Modelmentioning
confidence: 99%
See 3 more Smart Citations